The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cyto.b.21966
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory features associated with myeloperoxidase expression in pediatric B‐lymphoblastic leukemia

Abstract: Background: B-lymphoblastic leukemia (B-ALL) is the most common childhood malignancy, and its diagnosis requires immunophenotypically demonstrating blast B cell lineage differentiation. Expression of myeloperoxidase (MPO) in B-ALL is well-described and it has been recognized that a diagnosis of mixed phenotype acute leukemia should be made cautiously if MPO expression is the sole myeloid feature in these cases. We sought to determine whether MPO expression in pediatric B-ALL was associated with differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…In one study, MPO+ve patients tended to be older males without increased WBC counts or common B-ALL-related karyotypic findings, and showed an increased rate of relapse and a worse event-free survival than the patients with B-ALL who did not express MPO (Oberley et al, 2017). But another study that demonstrated a higher frequency of isoMPO expression, identified similar aberrant expression of myeloid markers and similar or even better clinical outcomes (as indicated by minimal residual disease) in the MPO+ve and -ve B-ALL, suggesting that these cases are not necessarily high-risk as a group and remain best classified as B-ALL rather than a separate entity (McGinnis et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In one study, MPO+ve patients tended to be older males without increased WBC counts or common B-ALL-related karyotypic findings, and showed an increased rate of relapse and a worse event-free survival than the patients with B-ALL who did not express MPO (Oberley et al, 2017). But another study that demonstrated a higher frequency of isoMPO expression, identified similar aberrant expression of myeloid markers and similar or even better clinical outcomes (as indicated by minimal residual disease) in the MPO+ve and -ve B-ALL, suggesting that these cases are not necessarily high-risk as a group and remain best classified as B-ALL rather than a separate entity (McGinnis et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Some investigators considered MPO expression in B-ALL as a diagnostic confounder in IHC (Du et al, 2020), or as a false positive FCM finding (Savasan et al, 2018). Nevertheless, the prognostic relations of this phenomenon were recently studied in pediatric B-ALL, and the data were controversial suggesting an association with higher risk and relapsing disease in some cohorts (Oberley et al, 2017, or better clinical outcomes in other cohorts (Raikar et al, 2018;McGinnis et al, 2020). To the best of our knowledge, a limited number of studies have investigated isoMPO in adult patients with B-ALL using IHC (Arber et al, 2001), therefore it may be of importance to address further studies in this field.…”
Section: Isolated Myeloperoxidase Immunohistochemical Expression In Bone Marrow Biopsy Depicts Clinical Outcomes In Adults With Typical Bmentioning
confidence: 99%
“…In fact, MPO expression could be observed in up to 22% of pediatric BALL patients. 14 Another concern in the diagnosis of this patient was the use of methylprednisolone before admission that might have lysed part of the blasts. Thus, the percentage of blasts in the bone marrow (15%) could have been underestimated hence suggestive of a diagnosis of mixed phenotypic acute leukemia (MPAL) according to the 2016 WHO guideline.…”
mentioning
confidence: 99%
“…Also in this issue, McGinnis and colleagues describe the clinical and laboratory correlates of myeloperoxidase (MPO) positivity by flow cytometry in a series of cases of B‐lymphoblastic leukemia (McGinnis et al, 2021). Although MPO is typically regarded as a specific marker of myeloid lineage, and in conjunction with B‐lineage antigens would raise the consideration of mixed phenotype acute leukemia (Porwit & Béné, 2019), MPO immunoreactivity should not automatically exclude a diagnosis of B‐lymphoblastic leukemia in an otherwise‐typical case (DiGiuseppe & Wood, 2019).…”
mentioning
confidence: 99%
“…Moreover, artifactual MPO positivity, which is well described in B‐lymphoblastic leukemia (Savaşan et al, 2018), should be excluded. Among the authors' findings were a higher proportion of hyperdiploidy and a lower proportion of ETV6‐RUNX1 among MPO‐positive cases compared with MPO‐negative cases (McGinnis et al, 2021). These findings complement other recently described immunophenotypic‐genotypic correlations in B‐lymphoblastic leukemia (Collins et al, 2021; Gudapati et al, 2020).…”
mentioning
confidence: 99%